Bedside ultrasound: a diagnostic tool for aortic dissection in the Emergency Department (2016)
The acute aortic syndrome can present as a characteristic clinical picture of a vascular emergency, or on the contrary as a completely atypical form, where the diagnosis challenges the emergency physician, leading to fatal mistakes by ignoring the diagnosis of this entity. In order to show the usefulness of ultrasound performed at the patient bedside in the diagnosis of aortic dissection, we described 9 cases of patients admitted to the emergency department and who were diagnosed with acute aortic syndrome, thanks to the initial ultrasonographic assessment made by residents and specialists in emergency medicine in one hospital in Bogotá, Colombia. This case report shows that ultrasound at the patient bedside, is a noninvasive diagnostic method, accessible and useful for early detection of this disease in the emergency services. © 2016 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular